2021
DOI: 10.3389/frwa.2021.689679
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Retention Capabilities of Extensive Green Roofs—New Design Approaches and an Open-Source Model

Abstract: Green roofs are a proven measure to increase evapotranspiration at the expense of runoff, thus complementing contemporary stormwater management efforts to minimize pluvial flooding in cities. This effect has been quantified by numerous studies, ranging from experimental field campaigns to modeling experiments and even combinations of both. However, up until now, most green roof studies consider standard types of green roof dimensions, thus neglecting varying flow length in the substrate. For the first time, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In general, ref. [42]'s research showed that designing a slope-free BGR reduces the runoff coefficient.…”
Section: Influence Of Roof System Configuration and Regional Climatic...mentioning
confidence: 99%
“…In general, ref. [42]'s research showed that designing a slope-free BGR reduces the runoff coefficient.…”
Section: Influence Of Roof System Configuration and Regional Climatic...mentioning
confidence: 99%
“…Green roofs tend to have a large effect on annual stormwater runoff and peak runoffs (Bengtsson, 2005), while the retention for extreme events is small (Stovin et al, 2013). LEAFlood can consider green roofs either in a simple way as land use with appropriate soil settings (Medina Camarena et al, 2022) or can be further developed and connected with the detailed CMF model setup of green roofs by Förster et al (2021). Additionally, a sensitivity analysis of the NbS could be conducted to improve the understanding of their performance and the impact of changing input on the model performance.…”
Section: Outlookmentioning
confidence: 99%
“…For example, two free software packages, SWMS_2D and Hydrus-1D, [48][49][50] apply Richards' equations to numerically derive soil water movement under unsaturated conditions, with model parameters based on specific soil textures. 51,52 Solving Richards' equations usually requires a high level of computational cost. As an alternative, simplified physically based infiltration equations are utilized by modelers.…”
Section: Overview Of Gr Modelsmentioning
confidence: 99%